Antenatal psychosocial assessment and depression screening in an Australian Private Hospital setting: A qualitative examination of women's perspectives. (December 2021) - Kohlhoff, Jane; Tooke, Sarah; Cibralic, Sara; Hickinbotham, R.; Knox, C.; Roach, V.; Barnett, B.
Abstract: Background: In Australia, clinical practice guidelines have been developed to support the implementation of antenatal psychosocial assessment and depression screening in routine clinical obstetric care. While there has been widespread uptake of such programs in Australian public hospitals, implementation in private hospitals has been slower. However, the situation in this regard may be changing, with the emergence of examples of midwife delivered screening programs in a number of private hospital settings. At present, patient experiences of these programs are largely unknown. Aim: The aim of this study was to gain feedback from women who participated in the 'Pre-admission midwife appointment' program at an Australian private hospital about their experiences of, and perspectives about, the program. Methods: Semi-structured interviews were conducted with 20 women ( M age 36.04 years, range 30-48) who had given birth to a child between 9 and 14 months prior to the interview ( M  = 11.87 months, SD  = 1.76) and who had attended the Pre-admission midwife appointment program during the pregnancy. Interviews were transcribed and analysed using an inductive thematic analysis approach with an essentialist-realistic theoretical framework. Findings: Data analysis revealed five major themes: 'increased awareness and support for perinatal mental health issues', 'enhanced quality of care provided at the hospital', 'experience with the midwife impacts perceptions of the program'; 'partners', and 'preparation for the program'. Discussion: This study provides useful information from the perspective of consumers, about a psychosocial assessment and depression screening program at an Australian private hospital. It highlights a number of program benefits for pregnant women, their partners, and the hospital, as well as factors facilitating program success.